Mana motuhake, Indigenous biopolitics and health. (March 2022) - Hokowhitu, Brendan; Oetzel, John; Jackson, Anne-marie; Simpson, Mary; Ruru, Stacey; Cameron, Michael; Zhang, Yingsha; Erueti, Bevan; Rewi, Poia; Nock, Sophie; Warbrick, Isaac
The majority of Indigenous health models do not directly acknowledge that health is a contested political space. Providing a Foucauldian analysis, this article suggests a function of biopower is to naturalise discourses such as the poor Māori health statistic to appear based on factual evidence and thus are apolitical. Employing Foucault's triad of power—sovereign, disciplinary and biopower—to understand the genealogy of Māori health, this article proffers mana motuhake (Māori political self-governance) as an appropriate health analytic because it, first, identifies Indigenous health as political and, second, because it recognises the disempowering role that colonialism has played in relation to Māori biopolitical self-governance. Hence, we suggest Māori health will be enhanced by mana motuhake and that research underpinned by Indigenous agency and self-governance resists biopower. The article references two Ageing Well National Science Challenge–funded research projects because they innovatively fundamentalise mana motuhake and politics to Indigenous health.